PERSPECTIVES OF RISK MANAGEMENT IN BANKING IN THE CONTEXT OF GLOBALIZATION AND CURRENT ECONOMIC CRISIS - Clara-Iulia, ZINCA (VOICULESCU) (Strategii Manageriale)
The banking industry, as well as the entire financial services industry, has experienced significant changes due to the development of new technologies, government deregulation and globalization, generating both opportunities and risks. The range of financial products and services offered by the banks expanded by adding new ones previously offered by other types of entities in the financial services industry. At the same time, competition continuously increased, from both banks and from other segments of the financial industry. Thus, from risk management under traditional financial intermediation, it was reached a dynamic, active and complex risk management in terms of reduced government regulations and in an environment with higher risks. Moreover, the economic crisis triggered in 2007 brought new challenges for the banking system, revealing many weaknesses in banks' risk management practices. By using appropriate research methods, such as document analysis, interpretative methods, this paper aims to identify the challenges of risk management in banking institutions in the current context of globalization and economic crisis, when the banks should focus on a better understanding of risk and on development of new best practices to ensure efficiency of risk management and better adaptation to dynamic changes of the economic environment